2020
DOI: 10.21203/rs.2.19734/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuromonitoring of delirium with quantitative pupillometry In sedated mechanically ventilated critically ill patients

Abstract: Background. Intensive care unit (ICU) delirium is a frequent secondary neurological complication in critically ill patients undergoing prolonged mechanical ventilation. Quantitative pupillometry is an emerging modality for the neuromonitoring of primary acute brain injury, but its potential utility in patients at risk of ICU delirium is unknown. Methods. This was an observational cohort study of medical-surgical ICU patients, without acute or known primary brain injury, who underwent sedation and mechanical ve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…As such, sepsis is frequently associated with brain dysfunction and impairment of cerebral autoregulation [12]. Few data are available on alterations in pupillary response using the automated pupillometry in these patients [48]; however, common pathways in brain and pupillary dysfunction, in particular of the cholinergic pathways, have been described in sepsis and might explain why we could observe a significant correlation only in this subgroup of patients. Nevertheless, the correlation was weak, as additional factors, such as sedative or analgesics, may significantly influence pupillary function in this setting as additional confounders [18,19].…”
Section: Discussionmentioning
confidence: 84%
“…As such, sepsis is frequently associated with brain dysfunction and impairment of cerebral autoregulation [12]. Few data are available on alterations in pupillary response using the automated pupillometry in these patients [48]; however, common pathways in brain and pupillary dysfunction, in particular of the cholinergic pathways, have been described in sepsis and might explain why we could observe a significant correlation only in this subgroup of patients. Nevertheless, the correlation was weak, as additional factors, such as sedative or analgesics, may significantly influence pupillary function in this setting as additional confounders [18,19].…”
Section: Discussionmentioning
confidence: 84%
“…The rate of delirium was recently estimated at 59% in critically ill patients without COVID-19 in our hospital. 27 Conversely, previous studies 8,9 available at the initiation of this project reported delirium rates over 80% in patients with COVID-19. We originally estimated a 2-sided α level of 0.05 and power of 80% to detect an absolute increase of 22% in the delirium incidence in patients with COVID-19; assuming an incidence of 60% in the control group and a 4:1 inclusion ratio (COVID-19:non-COVID-19), at least 180 patients including 144 with COVID-19 vs 36 without COVID-19 were to be enrolled.…”
Section: Discussionmentioning
confidence: 76%
“…Patients were considered delirious if they had at least 1 positive CAM-ICU, as in previous studies. 8,27,28 We also analyzed delirium length by retrieving the number of days with at least 1 positive CAM-ICU. Yet, these data were censored when the patients were discharged from the ICU.…”
Section: Outcome Variablesmentioning
confidence: 99%
“…The use of AIP for evaluating patients in both psychiatric and neurological settings extensively studied and has been used to predict outcomes after subarachnoid hemorrhage or cardiac arrest (Natzeder et al, 2019; Riker et al, 2020; Tamura et al, 2020). Recent studies have examined the relationship between CAM ICU scores and AIP indices (Favre et al, 2020; Yang et al, 2018). However, no study has investigated the relationship between the ICDSC score and AIP parameters.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The quantitative measurement of the pupillary light reflex by AIP represents an attractive tool for evaluating cholinergic activity in a clinical setting (Bower et al, 2021). In recent years, AIP has been suggested as an effective method for the early detection of delirium (Favre et al, 2020; Yang et al, 2018). Therefore, we hypothesized that AIP at ICU admission could predict the severity of delirium during the ICU stay.…”
Section: Introductionmentioning
confidence: 99%